Foreign Royal Nobles in the Neo Assyrian Empire - Koray Toptaş (Journal of Universal History Studies, 2024)
The Assyrian kings, who reached the peak of their power in the Near East between 934-612 BC, implemented various practices that would help them maintain their military and political dominance. Assyria's policy towards foreign royal captives, hostages, and refugees can also be considered within these practices. Assyria's policy was expected to preserve peace and keep some lands under control without war. The Assyrian kings carried the enemy kings and their family members whom they defeated as a result of military campaigns to Assyrian centres and captivated them, aiming to break the resistance of those regions and intimidate their enemies. In addition, Assyria aimed to gain some binding advantages to make the agreements permanent by taking hostages from the kings with whom it made agreements or made them swear allegiance. For this purpose, noble captives and hostages were subjected to Assyrian education and were tried to turn into allies who could be appointed as rulers of their countries in the future. Assyrian kings also wanted to establish their relations with these kingdoms on a binding and permanent basis by including the daughters of enemy or allied kings in their harems. Finally, they protected the noble people who took refuge in them in Assyrian cities and even helped them to become kings in their countries, depending on the changes in the political situation. Thus, the Assyrian kings thought that they could create rulers loyal to themselves. Based on cuneiform documents, this study investigates the Assyrian practice of taking captives and hostages, the position and status of foreign princesses sent to the Assyrian court, and the place of refugees in Assyrian policy. The study aims to reveal all aspects of Assyria's policy and to draw a portrait of the lives of foreign royals in the Assyrian court and cities. The primary sources used in this study are the royal inscriptions and the Assyrian state archive.